Attitudes of Students towards Entrepreneurship in Higher Education Institutions of Chitwan District (Shaheed Smriti Journal, 2024)
This study aims to explore students' attitudes toward entrepreneurship education in Chitwan District, Nepal, focusing on their practical, cognitive, and affective perspectives. Using a quantitative research design, data were collected from a sample of 200 students enrolled in entrepreneurship programs across several colleges. A structured questionnaire was administered to assess students' attitudes regarding entrepreneurship education, including their enthusiasm, knowledge, and emotional connection to self-employment. Data were analyzed using descriptive statistics to identify patterns and trends. The findings reveal that while students show a strong interest in entrepreneurship, with high motivation to pursue self-employment, they feel underprepared for practical application. Despite a solid understanding of business planning and financing, students report low levels of support for applying their knowledge in real-world contexts. The study concludes that while entrepreneurship education is positively received, more hands-on experiences, such as guest speaker interactions and practical business activities, are essential to bridge the gap between theory and practice.